Selection of Posture for Time-Trial Cycling Events - Alejandra P. Polanco; Luis E. Muñoz; Alberto Doria; Daniel R. Suarez (Applied Sciences, 2020)
Cyclists usually define their posture according to performance and comfort requirements. However, when modifying their posture, cyclists experience a trade-off between these requirements. In this research, an optimization methodology is developed to select the posture of cyclists giving the best compromise between performance and comfort. Performance was defined as the race time estimated from the power delivery capacity and resistive forces. Comfort was characterized using pressure and vibration indices. The optimization methodology was implemented to select the aerobars’ height for five cyclists riding on 20-km time-trial races with different wind speed and road grade conditions. The results showed that the reduction of the aerobars’ height improved the drag area (−10.7% ± 3.1%) and deteriorated the power delivery capacity (−9.5% ± 5.4%), pressure on the saddle (+16.5% ± 11.5%), and vibrations on the saddle (+6.5% ± 4.0%) for all the tested cyclists. It was observed that the vibrations on the saddle imposed the greatest constraint for the cyclists, limiting the feasible exposure time and, in some cases, modifying the result obtained if the posture was selected considering only performance. It was concluded that optimal posture selection should be performed specifically for each cyclist and race condition due to the dependence of the results on these factors.